The VMC Survey - XII. Star cluster candidates in the Large Magellanic Cloud - Piatti, Andres Eduardo (2014)
Context. In this work we analyse Colour-Magnitude Diagrams (CMDs) of catalogued star clusters located in the Large Magellanic Cloud (LMC), from a Y JKs photometric data set obtained by the Visible and Infrared Survey Telescope for Astronomy (VISTA) survey of the Magellanic Clouds system (VMC). Aims. We studied a total of 98 objects of small angular size, typically 11.6 pc in diameter projected towards both uncrowded tile LMC 8 8 and crowded tile LMC 5 5. They populate relatively crowded LMC fields with significant fluctuations in the stellar density, the luminosity function, and the colour distribution as well as uncrowded fields. This cluster sample is aimed at actually probing our performance in reaching the CMD features of clusters with different ages in crowded/uncrowded fields. Methods. We applied a subtraction procedure to statistically clean the cluster CMDs from field star contamination. We then matched theoretical isochrones to the background-subtracted CMDs to determine the ages and metallicities of the clusters. Results. We estimated the ages of 65 clusters, which resulted to be in the age range 7.3 < log(t/yr) < 9.55. We also classified as chance grouping of stars 19 previoulsy catalogued clusters, two possible cluster-like asterisms, and one unresolved cluster. For other 8 objects, we could not find a clear star concentration in the Ks images either, so we quoted them as cluster-like asterisms. Finally, we found two previously catalogued single star clusters to be unresolved background galaxies (KMHK747, OGLE366), and one to be a triple cluster system (BSDL 2144).